Models of relationship between emotional, spiritual, physical and social intelligence, resilience and burnout among high school teachers - Ismail, Abdul Aziz; Sulaiman, Tajularipin; Roslan, Samsilah (Horizon Research Publishing, 2020)
Burnout is a condition that can affect a person’s work performance. Among the internal factors that contribute to burnout are emotional intelligence, spiritual intelligence, social intelligence, physical intelligence and resilience. This study explores the relationship among these internal factors toward the occurrence of burnout. A relationship model between variable of study was created based on the findings of the study. Instruments related to emotional, spiritual, social and physical intelligence and burnout have been distributed to 377 students of secondary school teachers throughout Selangor as a sample of chosen research using random-stratified sampling and cluster sampling. This study utilizes two approaches in analyzing data, which consist of descriptive statistics of IBM SPSS software statistics 22.0 and inferential statistics using advanced modeling analysis Structured equations (SEM) through the software Analysis of Moment Structure (AMOS) 22.0. The results of correlation analysis have shown that there is direct relationship for all intelligence factors against burn out. All variables have affected burnout except social intelligence. The findings of the study to demonstrate a model of emotional intelligence, social intelligence, physical intelligence, spiritual intelligence and resilience with burnout have reached the concurrence value. Teachers equip themselves with the intelligence and have resilience in carrying out its duties to increase the students ‘ achievement, thereby encouraging their excellence. The predictor of emotional, spiritual, physical intelligence and burn-outs is an important indicator to certain stakeholder such as Ministry of Education Malaysia to improve vital elements to choose a teacher and courses that should be implemented to the teacher to prevent burnout from occurring.